The bioavailability and airway clearance of the steroid component of budesonide/formoterol and salmeterol/fluticasone after inhaled administration in patients with COPD and healthy subjects: a randomized controlled trial - Dalby, Chris (BioMed Central, 2009)
BACKGROUND: Airway absorption and bioavailability of inhaled corticosteroids (ICSs) may be influenced by differences in pharmacokinetic properties such as lipophilicity and patient characteristics such as lung function. This study aimed to further investigate and clarify the distribution of budesonide and fluticasone in patients with severe chronic obstructive pulmonary disease (COPD) by measuring the systemic availability and sputum concentration of budesonide and fluticasone, administered via combination inhalers with the respective long-acting β(2)-agonists, formoterol and salmeterol. METHODS: This was a randomized, double-blind, double-dummy, two-way crossover, multicenter study. Following a run-in period, 28 patients with severe COPD (mean age 65 years, mean forced expiratory volume in 1 second [FEV(1)] 37.5% predicted normal) and 27 healthy subjects (mean age 31 years, FEV(1 )103.3% predicted normal) received two single-dose treatments of budesonide/formoterol (400/12 μg) and salmeterol/fluticasone (50/500 μg), separated by a 4–14-day washout period. ICS concentrations were measured over 10 hours post-inhalation in plasma in all subjects, and over 6 hours in spontaneously expectorated sputum in COPD patients. The primary end point was the area under the curve (AUC) of budesonide and fluticasone plasma concentrations in COPD patients relative to healthy subjects. RESULTS: Mean plasma AUC values were lower in COPD patients versus healthy subjects for budesonide (3.07 μM·hr versus 6.21 μM·hr) and fluticasone (0.84 μM·hr versus 1.50 μM·hr), and the dose-adjusted AUC (geometric mean) ratios in healthy subjects and patients with severe COPD for plasma budesonide and fluticasone were similar (2.02 versus 1.80; primary end point). In COPD patients, the T(max )and the mean residence time in the systemic circulation were shorter for budesonide versus fluticasone (15.5 min versus 50.8 min and 4.41 hrs versus 12.78 hrs, respectively) and C(max )was higher (1.08 μM versus 0.09 μM). The amount of expectorated fluticasone (percentage of estimated lung-deposited dose) in sputum over 6 hours was significantly higher versus budesonide (ratio 5.21; p = 0.006). Both treatments were well tolerated. CONCLUSION: The relative systemic availabilities of budesonide and fluticasone between patients with severe COPD and healthy subjects were similar. In patients with COPD, a larger fraction of fluticasone was expectorated in the sputum as compared with budesonide. TRIAL REGISTRATION: Trial registration number NCT00379028